Impoliteness strategies implied among characters of The Simpsons Movie - Meylana Ardhy; Issy Yuliasri; Fahrur Rozi (Universitas Negeri Semarang, 2024)
The basic rule in communicating is to respect the interlocutor so that the process of communication can run smoothly. Then, the concept of impoliteness by Culpeper (1996) appears and raises new views. Rather than protecting the face of the interlocutor, the concept of impoliteness is used to attack. In communication, impoliteness should be avoided because of its potential to cause conflict. Uniquely, impoliteness is used in the entertainment sector, such as in The Simpsons Movie. With various impoliteness strategies combined with varied implementations, impoliteness that has a negative impression becomes something entertaining. This research aims to 1) Explain the use of impoliteness strategies and 2) explain its function in The Simpsons Movie. The theories used are Culpeper (1996) and (2011), while the method is descriptive qualitative. The detailed findings are bald-on-record 14%, positive impoliteness 42%, negative impoliteness 32%, sarcasm 8%, and withhold politeness 4%, which each strategy has its uniqueness. From this study, it is found that there are various implementations, combinations of delivery, and functions of impoliteness. The use of the impoliteness function plays an important role. The utilization of affective, coercive, and entertainment functions provokes the emotions of the interlocutor and audience to make the movie interesting.